A comprehensive study of metal-coated short carbon fibers, graphite particles, and hybrid fillers for induction heating. (March 2020) - Muddassir, Muhammad; Duhovic, Miro; Gurka, Martin
Induction heating or welding can be performed by considering the combined effect of ferromagnetic heating due to magnetic hysteresis losses and eddy current heating due to conductive material. Nonconducting thermoplastic composite parts can be joined or welded by induction heating using a susceptor sheet filled with nickel-coated carbon fibers (NiCCFs) and nickel-coated graphite particles (NiCGPs) or both with polypropylene (PP) thermoplastic matrix. Above the percolation threshold, NiCCFs can serve as conductive materials and nickel coating will provide the ferromagnetic heating. NiCCF/PP and NiCCF/NiCGP/PP susceptor sheets were developed via melt mixing using a twin-screw extruder and sheets were produced by Calendering process. Induction heating tests were performed on a circular pancake coil and at frequencies below 1 MHz. In induction heating, fiber heating by Joule loss, junction heating (i.e. dielectric heating and contact resistance heating), as well as magnetic hysteresis effect were observed in both the cases. Heating in hybrid filler was higher at lower filler concentrations; however, with higher concentrations, heating reduced. Reduction in induction heating maybe due to a reduction in electrical conductivity was observed. Electrical conductivity was measured in fibers direction by a Keithley electrometer using a four-point measuring method and temperature was measured by an infrared thermal camera. Microstructure characterization was performed by X-ray computed microtomography and light microscopy.